CARBON STOCK ESTIMATION IN FABACEAE TREE STANDS WITHIN THE URBAN FORESTSOF BANDA ACEH - Wira Dharma; Yekki Yasmin; Nada Ariqah; Essy Harnelly; Alia Rizki; Amirunnas; Anita Rauzana; Rahmad Zakaria (SEAMEO BIOTROP, 2026)
ARTICLE HIGHLIGHTS- Identified four Fabaceae tree species across three urban forests in Banda Aceh.- Total estimated potential carbon stock in Fabaceae stands reached 292.08 tonnes/ha.- Trembesi Urban Forest contributed the highest carbon stock at 124.14 tonnes/ha.- Samanea saman is the dominant carbon contributor, storing 248.44 tonnes/ha.- Stem diameter serves as a highly reliable predictor for urban tree carbon stocks.ABSTRACTUrban forests play a crucial role in absorbing carbon emissions through the biomass carbon stocks stored in vegetation. The Fabaceae family is a potential group of tree for carbon storage, but its contribution to the Banda Aceh urban forest area remains understudied. This study aims to identify tree species from the Fabaceae family and estimate the potential carbon stocks stored in stands of this family in the Banda Aceh urban forest. The study was conducted in three urban forest locations: Putroe Phang (PP), Trembesi (TR), and BNI Urban Forests (BNI). Carbon stocks were estimated using a non-destructive method with an allometric equation approach. The results showed that there were four tree species from the Fabaceae family, namely Samanea saman, Pterocarpus indicus, Tamarindus indica, and Delonix regia, with a total of 197 individuals recorded. The total potential carbon stocks stored in Fabaceae stands in the three urban forest areas reached 292.08 tons/ha, with the largest contribution coming from the Trembesi (TR) Urban Forest at 124.14 tons/ha. The tree species that provides the largest contribution to carbon biomass is Samanea saman with an estimate of 248.44 tons/ha.